Determination Of Commercial Banks’ Profitability In Indonesia - Syahid, Muhammad; Elzaanin, Amina A.A; Purnamasari, Sinta Ayu; Sari, Wahyu Nita; Badriah, Siti (Jurnal Ilmiah Ekonomi Islam, 2024)
This research explores the relationship between specific characteristics of banks and their profitability. Bank profitability is related to external and internal factors regarding assets, capital, and loans in general. This study is mainly concerned with internal factors that influence the profitability of commercial banks in Indonesia. 55 Banks including 51 National Private Banks, and 4 Public Sector Banks. Data taken in its entirety from the Financial Services Authority website in 2023. Using the Ordinary Least Square (OLS) method with the help of Stata software. The results of the research show that in a simultaneous test, the asset, capital, and loan variables have a positive and significant effect on profitability with the figure obtained being 78% while other variables explain the rest, while in a partial test, the asset and bank loan variables harm bank profitability, and only the capital variable which is positively related to profitability by 86%, and the rest is explained by other variables. This shows that large banks may face similar challenges as marginal profits decrease as targets must be achieved because in fact the bank Asset and Loan variables are also expected to be the main source of income so that they have a positive relationship with bank performance.